Capturing in vivo RNA transcriptional dynamics from the malaria parasite Plasmodium falciparum - Painter, Heather J.; Carrasquilla, Manuela; Llinás, Manuel (Genome Research, 2017)
To capture the transcriptional dynamics within proliferating cells, methods to differentiate nascent transcription from preexisting mRNAs are desired. One approach is to label newly synthesized mRNA transcripts in vivo through the incorporation of modified pyrimidines. However, the human malaria parasite, Plasmodium falciparum, is incapable of pyrimidine salvage for mRNA biogenesis. To capture cellular mRNA dynamics during Plasmodium development, we engineered parasites that can salvage pyrimidines through the expression of a single bifunctional yeast fusion gene, cytosine deaminase/uracil phosphoribosyltransferase (FCU). We show that expression of FCU allows for the direct incorporation of thiol-modified pyrimidines into nascent mRNAs. Using developmental stage-specific promoters to express FCU-GFP enables the biosynthetic capture and in-depth analysis of mRNA dynamics from subpopulations of cells undergoing differentiation. We demonstrate the utility of this method by examining the transcriptional dynamics of the sexual gametocyte stage transition, a process that is essential to malaria transmission between hosts. Using the pfs16 gametocyte-specific promoter to express FCU-GFP in 3D7 parasites, we found that sexual stage commitment is governed by transcriptional reprogramming and stabilization of a subset of essential gametocyte transcripts. We also measured mRNA dynamics in F12 gametocyte-deficient parasites and demonstrate that the transcriptional program required for sexual commitment and maturation is initiated but likely aborted due to the absence of the PfAP2-G transcriptional regulator and a lack of gametocyte-specific mRNA stabilization. Biosynthetic labeling of Plasmodium mRNAs is incredibly versatile, can be used to measure transcriptional dynamics at any stage of parasite development, and will allow for future applications to comprehensively measure RNA-protein interactions in the malaria parasite.